1991
DOI: 10.1159/000120602
|View full text |Cite
|
Sign up to set email alerts
|

Current Management of Choroid Plexus Carcinoma in Children

Abstract: Eleven children with choroid plexus carcinoma are reviewed with respect to presentation, radiographic diagnosis, treatment and pathologic histology. These cases accumulated over a 33-year period and represent 39% of all of our choroid plexus tumors (n = 28). Characteristically, choroid plexus carcinomas are associated with a poor prognosis for long-term survival. Unfortunately, efforts at total resection are hindered in part by the extreme vascularity of the tumor which itself may be of considerable volume. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 8 publications
1
40
0
4
Order By: Relevance
“…Gross total resection is the goal, and pharmacologic intervention including chemotherapy and radiation therapy remains controversial, as this treatment is not curative [3]. We would like to share this unusual case with the medical community to increase clinical understanding in the management and treatment of this malignant tumor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gross total resection is the goal, and pharmacologic intervention including chemotherapy and radiation therapy remains controversial, as this treatment is not curative [3]. We would like to share this unusual case with the medical community to increase clinical understanding in the management and treatment of this malignant tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Despite multiple reports about the benefits of chemotherapy and radiation therapy, medical treatment for this tumor type is not curative [3]. In a study of an eight month old infant who achieved remission with chemotherapy, local tumor recurrence was reported 13 months after initiation of treatment [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aggressive resection may be very challenging because of the invasive nature and extreme vascularity of CPCs. In order to achieve a GTR, some authors have suggested a staged approach through the use of neoadjuvant chemotherapy following biopsy of disease [98,101]. For those patients whose tumors are completely resected at diagnosis, the role of adjuvant chemotherapy, radiation therapy, or both remains controversial [100,[103][104][105].…”
Section: Choroid Plexus Tumorsmentioning
confidence: 99%